Establishing Consensus for Essential Elements in Returning to Learn Following a Concussion. (16th September 2020) - McAvoy, Karen; Eagan‐Johnson, Brenda; Dymacek, Rosalie; Hooper, Stephen; McCart, Melissa; Tyler, Janet
ABSTRACT: BACKGROUND: Returning to learn following a concussion is the process of managing a student's recovery during the school day by implementation of academic supports with varying intensity. Due to a lack of consensus or even guidance on Return to Learn, this paper set out to establish cross discipline consensus on some essential elements of Return to Learn using a Delphi method. METHODS: Sixteen national organizations participated in a Delphi process to reach consensus on overarching themes of Return to Learn focused on: returning a student to school, composition of the school‐based concussion management team, progress‐monitoring, educational safeguards, neuropsychological testing, and legislation. Two rounds of questionnaires were disseminated via email using a Delphi process. Consensus was established during round 2. RESULTS: Twelve national organizations were able to reach consensus and endorse 13 essential elements of Return to Learn following a concussion. CONCLUSIONS: There continues to be limited research on concussion Return to Learn leading to confusion in the field. In this paper, we demonstrate consensus on a number of essential elements, from a wide variety of professional disciplines who participate in the care of students following a concussion, as a starting place for some guidance on Return to Learn.